Simulasi Alur Pelayanan Rawat Jalan (Poliklinik) di Rumah Sakit Menggunakan Software ProModel - Yuli Dwi Astanti; Irwan Soejanto; Intan Berlianty (OPSI, 2020)
Hospital is a community service center that has a vital role. Hospital activities related to human life make the hospital as a system that must provide excellent service for visitors (patients). In fact the excellent service is not easy to do because of the many components involved in the system. Components or variables in the system are prbabilistik or uncertain. To maintain the quality of hospital services, an action is needed to evaluate, analyze and improve the system, especially the service system for patients. Simulation is one of the tools that can be used to evaluate, analyze and test changes to the system to get better results. In this study, simulation will be carried out on the outpatient or polyclinic service system in RSUX using simulations with the help of software promodel. From the simulation results it is known that the simulation model is valid and can be used to evaluate the system. In this study, a trial was conducted to change the number of servers in the pricing section to obtain a smaller idle process.